Ekstraksi dan Identifikasi Komponen Utama Pasir Putih dari Desa Marinsow Kabupaten Minahasa Utara dengan Pengujian XRF dan XRD - Billy Gabriel Langi; Meyti J Rampe; Soenandar M T Tengker (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
North Sulawesi is one of the regions in Indonesia which has a wealth of natural resources which is quite abundant, one of the natural potential that can be utilized is White sand. White sand has a composition that is SiO2, CaO, Fe2O3, TiO2, MgO. This study aims to identify the composition of the main components of white sand through XRF testing and the results of extraction of white sand from Marinsow village using the alkaline fusion method, NaOH solution for extracting and crystallizing the formation of silica crystals and tested using XRD testing to determine the crystal characteristics. Extraction and testing processes have been carried out using XRF and XRD on white sand samples taken in Marinsow Village, North Minahasa Regency. The results of the identification of the components of the white sand constituents through XRF testing namely CaO is the largest main component of the white sand compilers in the village of Marinsow which is as much as 89.97%. The content of SiO2 compounds in white sand (Marinsow) is as much as 1.41%. Other components found in white sand from Marinsow village, North Minahasa Regency include MgO as much as 5.85%, SrO as much as 2.31%, Fe2O3 as much as 0.277 %, TiO2 is 0.079%, Cr2O3 is 0.032%, Nb2O5 is 0.0238%, MoO3 is 0.0159%, SnO2 is 0.0082%, Sb2O3 is 0.0079% and RuO4 is 0.0074%. The results of XRD testing on white sand taken in the village of Marinsow give results that white sand has a calcite crystal structure (CaO) and for the SiO2 silica component is quartz.